(untitled) (Archives of Clinical Psychiatry, 2013)
OBJECTIVE: The Parenting Alliance Measure (PAM) assesses the quality interparental relationship in childbearing. The present study aims to validate the Portuguese version of this measure and also develop and examine the psychometric properties of a 6-items short-version of PAM (PAM-R). METHOD: The sample was composed by 182 parents (63% mothers), 72 of them filled in a questionnaire regarding psychological adjustment problems of their children. RESULTS: Confirmatory Factorial Analyses did not support the structure of the PAM's two tested models. However, PAM-R showed excellent fit. Specification errors were not found in the tested unidimensional model that supports the factorial validity of the short-version of PAM. The PAM-R showed excellent values of internal consistency and a significant and negative correlation between PAM-R and children's behavior problems was found. DISCUSSION: PAM-R emerges as a measure that enables the assessment of the effects of the family dimensions on children's psychological development and adjustment in primary health care settings.